HUBUNGAN DUKUNGAN KELUARGA DENGAN TINGKAT DEPRESI PADA LANSIA - Budi Kristanto; Rika Fitri Agustina (Sekolah Tinggi Ilmu Kesehatan Panti Kosala, 2018)
Background : The incidence of depression in elderly people in Indonesia is currently high.Indonesia has entered the era of elderly population. In 2009, the number of people agedover 60 years about 7.18%. Depression is a major mental health problem today. This isvery important because the incidence of depression will badly affects the productivity ofpeople particulary in a developing society.Research purposes : This research was generally aimed to find out the relationshipbetween family support and depression level in elderly as well as specifically to identifyfamily support for elderly and identify depression level in elderly.Subject : Research respondents were elderly people aged 60 years and over in TelukanVillage Sukoharjo District.Method : This research is a correlation research with cross sectional approach to analyzethe relationship betwen family support with depression level in elderly in Telukan VillageSukoharjo District. In this study the researcher used a saturated sampling technique inwhich all members of the population was used as a research respondent accounted for60.Research result : The majority of respondents who good support from their family was58.3% while the rest 41.7% got less support. The majority of were normal category (80%)while those with mild depression by 20%. The results of analysis with PearsonCorrelation obtained p value = 0.000 and value r = - 0.559.Conclusion : There is a significant relationship between family support and the incidenceof depression in the elderly. The higher the family support the lower the incidence ofdepression in the elderly.Keywords: depression, family support, elderly